Bioremediation of organic pollutants by white rot fungal cytochrome P450: The role and mechanism of CYP450 in biodegradation. (August 2022) - Lin, Shuqi; Wei, Jinchao; Yang, Bentao; Zhang, Meng; Zhuo, Rui
Abstract: Cytochrome P450 (CYP450) is a well-known protein family that is widely distributed in many organisms. Members of this family have been implicated in a broad range of reactions involved in the metabolism of various organic compounds. Recently, an increasing number of studies have shown that the CYP450 enzyme also participates in the elimination and degradation of organic pollutants, by white rot fungi (WRF), a famous group of natural degraders. This paper reviews previous investigations of white rot fungal CYP450 involved in the biodegradation of organic pollutants, with a special focus on inhibitory experiments, and the direct and indirect evidence of the role of white rot fungal CYP450 in bioremediation. The catalytic mechanisms of white rot fungal CYP450, its application potential, and future prospect for its use in bioremediation are then discussed. Graphical abstract: Image 1 Highlights: Reviewed the role of CYP450s in the biodegradation of organic pollutants by WRF. The inhibitory experiments and the evidence for WRF CYP450s in bioremediation were presented. Discussed the catalytic mechanisms of WRF CYP450s in organic pollutants biodegradation.